Adaptation of the "ten questions" to screen for autism and other neurodevelopmental disorders in Uganda. (May 2014) - Kakooza-Mwesige, Angelina; Ssebyala, Keron; Karamagi, Charles; Kiguli, Sarah; Smith, Karen; Anderson, Meredith C; Croen, Lisa A; Trevathan, Edwin; Hansen, Robin; Smith, Daniel; Grether, Judith K
Neurodevelopmental disorders are recognized to be relatively common in developing countries but little data exist for planning effective prevention and intervention strategies. In particular, data on autism spectrum disorders are lacking. For application in Uganda, we developed a 23-question screener (23Q) that includes the Ten Questions screener and additional questions on autism spectrum disorder behaviors. We then conducted household screening of 1169 children, 2–9 years of age, followed by clinical assessment of children who screened positive and a sample of those who screened negative to evaluate the validity of the screener. We found that 320 children (27% of the total) screened positive and 68 children received a clinical diagnosis of one or more moderate to severe neurodevelopmental disorders (autism spectrum disorder; cerebral palsy; epilepsy; cognitive, speech and language, hearing, or vision impairment), including 8 children with autism spectrum disorders. Prevalence and validity of the screener were evaluated under different statistical assumptions. Sensitivity of the 23Q ranged from 0.55 to 0.80 and prevalence for ≥1 neurodevelopmental disorders from 7.7/100 children to 12.8/100 children depending on which assumptions were used. The combination of screening positive on both autism spectrum disorders and Ten Questions items was modestly successful in identifying a subgroup of children at especially high risk of autism spectrum disorders. We recommend that autism spectrum disorders and related behavioral disorders be included in studies of neurodevelopmental disorders in low-resource settings to obtain essential data for planning local and global public health responses.